Psychometric properties of the Chinese version of the Eating Attitudes Test (EAT-26) in young female patients with eating disorders in mainland China - Kang, Qing; Chan, Raymond C.K.; Li, Xiaoping; Arcelus, Jon; Yue, Ling; Huang, Jiabin; Gu, Lian; Fan, Qing; Zhang, Haiyin; Xiao, Zeping; Chen, Jue (Wiley, 2017)
The study aimed to investigate the reliability and validity of the Chinese version of the eating attitudes test (EAT-26) among female adolescents and young adults in Mainland China. This scale was administered to 396 female eating disorder patients and 406 noneating disorder healthy controls, in addition 35 healthy controls completed a retest after a 4-week intervals. Tests for reliability, convergent validity and receiver operating characteristic analysis were performed to detect the psychometric properties. The EAT-26 demonstrated good internal consistency (Cronbach's alpha = 0.822–0.922), test–retest reliability (interclass correlation coefficient = 0.817) and convergent validity(r = 0.450–0.750). The receiver operating characteristic analysis showed that the cut-off 14 for anorexia nervosa and 15 for bulimia nervosa represented good compromises with approximate sensitivity (0.66–0.68) and specificity (0.85–0.86). Our findings provided evidence that the Chinese version of the EAT-26 was a psychometrically reliable and valid self-rating instrument for identifying people suffering from an eating disorder in Mainland China. A clinical cut-off range between 14 and 15 could be used, but caution should be exercised because of the low sensitivity of the tool.